Camrelizumab versus placebo in combination with gemcitabine and cisplatin as first-line treatment for recurrent or metastatic nasopharyngeal carcinoma (CAPTAIN-1st): a multicentre, randomised, double-blind, phase 3 trial. Issue 8 (August 2021) - Yang, Yunpeng; Qu, Song; Li, Jingao; Hu, Chaosu; Xu, Mingjun; Li, Weidong; Zhou, Ting; Shen, Liangfang; Wu, Hui; Lang, Jinyi; Hu, Guangyuan; Luo, Zhanxiong; et al.
Summary: Background: The addition of camrelizumab to gemcitabine and cisplatin showed promising activity as first-line therapy in patients with recurrent or metastatic nasopharyngeal carcinoma in a phase 1 trial. We therefore compared camrelizumab plus gemcitabine and cisplatin with placebo plus gemcitabine and cisplatin in a randomised phase 3 trial. Methods: In this randomised, double-blind, phase 3 trial done at 28 hospitals in China, patients were eligible if they were aged 18–75 years, had an Eastern Cooperative Oncology Group (ECOG) performance status of 0–1, and had previously untreated recurrent or metastatic nasopharyngeal carcinoma. Patients were randomly assigned (1:1; using an interactive web-response system with a block size of four) to receive either camrelizumab (200 mg on day 1) or matching placebo intravenously, plus gemcitabine and cisplatin (gemcitabine 1000 mg/m 2 on days 1 and 8; cisplatin 80 mg/m 2 on day 1) intravenously every 3 weeks for four to six cycles, followed by maintenance therapy with camrelizumab or placebo, until radiographic progression, unacceptable toxicity, start of new anticancer treatment, investigator decision, or withdrawal of consent. Stratification factors used in randomisation were liver metastases, previous radical concurrent chemoradiotherapy, and ECOG performance status. The allocation sequence was generated by an independent randomisation group. The primary endpoint was progression-free survival per independent review committee. The significance threshold for independent review committee-assessed progression-free survival was p=0·0086 (one-sided) at the interim analysis. Efficacy and safety analyses included all patients who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, NCT03707509, and is closed for enrolment but is ongoing. Findings: Between Nov 13, 2018, and Nov 29, 2019, 343 patients were screened and 263 were eligible and were randomly assigned to the camrelizumab group (n=134) or placebo group (n=129). At the prespecified interim analysis (June 15, 2020), independent review committee-assessed progression-free survival was significantly longer in the camrelizumab group (median 9·7 months [95% CI 8·3–11·4]) than in the placebo group (median 6·9 months [5·9–7·3]; hazard ratio 0·54 [95% CI 0·39–0·76]; one-sided p=0·0002). As of Dec 31, 2020, the most common grade 3 or worse adverse events of any cause were decreased white blood cell count (89 [66%] of 134 patients in the camrelizumab group vs 90 [70%] of 129 patients in the placebo group), decreased neutrophil count (86 [64%] vs 85 [66%]), anaemia (53 [40%] vs 57 [44%]), and decreased platelet count (53 [40%] vs 52 [40%]). Serious adverse events were reported in 59 (44%) of 134 patients in the camrelizumab group and 48 (37%) of 129 patients in the placebo group. Treatment-related deaths occurred in five (4%) patients in the camrelizumab group (two unknown cause of death, one multiple organ dysfunction syndrome, one pharyngeal haemorrhage, and one arrhythmia) and one (<1%) patient in the placebo group (unknown cause of death). Interpretation: Our findings suggest that camrelizumab plus gemcitabine and cisplatin could be a new standard of care for patients with recurrent or metastatic nasopharyngeal carcinoma in the first-line setting. Longer follow-up is needed to confirm this conclusion. Funding: Jiangsu Hengrui Pharmaceuticals (formerly Jiangsu Hengrui Medicine). Translation: For the Chinese translation of the abstract see Supplementary Materials section.